Coping strategies of schizophrenic patients referring to psychiatry clinics at hospitals affiliated to universities of medical sciences in Tehran - Ranjbar, F; Tamizi, Z; Yaghmai, F; Alavi-Majd, H; Falahi-Khoshknab, M (Advances in Nursing & Midwifery, 2008)
Abstract Background Schizophrenia is the most disabling mental disorder and patients with it experience much stress. Coping strategies, therefore, play a significant period in this regard and these patients may have difficulty in applying them. They usually use ineffective coping strategies. Purpose This descriptive study was conducted to determine coping strategies in schizophrenic patients referring to psychiatry clinics at hospitals affiliated to universities of medical sciences in Tehran in 2006. Methods 90 schizophrenic patients were selected at two stages by quota and convenience sampling methods. The Ways of Coping Questionnaire was used0. for data collection after identifying its content and face validities and its reliability by internal consistency. Data were collected by self-report method and review of medical records. Results Findings showed that “resignation” (50.11%) and “self - soothing” (47.06%) were the first and second common strategies respectively. “Considering (41.38%),” “Positive reappraisal (40.86%),” “Ignoring (40.67%)” and “Acting (37.03)” were the third common strategies. Most subjects also used “Avoidance” and the minority of them applied “Problem-oriented” strategies. Conclusion Most subjects used “Avoidance” coping strategy. Keywords: Schizophrenic patients, Coping strategy, Psychiatry clinic.